Developmental pathways: the hydroelectric power plant Belo Monte as an illustrative case of the complexity involved - Souza, Angelita Matos [UNESP] (Revues Org, 2016)
The objective is to address the developmental debate sparked by the economic policy of the Workers Party (PT) government, focusing on the developmental and environmentalist views and then discuss the Belo Monte hydroelectric plant as an illustrative case of the complexity of the state intervention processes that focus on advancing infrastructure through large projects, for the purposes of development. From this perspective, it is important highlight the rescue of political isolation of populations placed in traditional ways of life and, in addition to gains in political activism, point to socioeconomic gains in parallel with the barbarism involved in the construction of the plant on the Xingu River, Para, Brazil.
Keywords: Development; Belo Monte; Popular Mobilization